Perikanan laut di Karisidenan Besuki apad akhir abad XIX sampai pertengahan abad XX = The Sea Fishery in Besuki Residency in the Late 19th Centurythe Middle of 20th Century - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT This thesis discusses the sea fishery in Residency Besuki, East Java in the late ninetieth century until the middle of twentieth century. Beside from agriculture, Besuki people depend their from catching fish in the sea. In the decade of 1900, Java imported many fishes from other country, but Besuki did not consume many salted fishes because they can do it by themselves. The economic network of fishermen in Besuki is an interesting problem to be researched. The problems are as follow: 1. How was the condition and the technology mode in catching fish in Besuki? 2. How was the organization network of fishermen in Besuki? 3. How big was the fishermen's productivity in the region? 4. How far was the distribution of fish? This research uses history method, refering to a set of arrangements and principles for gathering historic sources effectively, evaluating critically and finally presenting the synthesis historiografy. The maritime condition in Besuki is rich in many kind of fish, a benefit condition for the fishermen. The mode of fish catching in offshore and seashore used by the fishermen was depended to the environment. In the offshore they used "faring payang tengah" (a kind of net) and fishhook. And for seashore, they used "faring payang pinggir," net, bubu or plaited rattan fish trap, banjang or fishing platform. Even for attach the fish, they used torch and the druklight lamp. They used some kind of ships such as "ma-yang," "jukung," "jukung mancingan" and "sampan." Their operation was organized in which the land master had an exploitative and symbiotic relationship to the sea master, ship crews and fish vendors. Ships and the tools are part of fish catching technology. Beside of that there was a fish processing like sating, drying and fish preservation. The fishermen's production in Besuki had a sign of improvement, even it tended to be subsistent. In the early twentieth century, fishermen in Java and Besuki declined. From cathing fish in the offshore, then they only catched fish in the seashore. But until the decade of 1940's, their production was more higher than from any fish auction in Indonesia like in Besuki, Panarukan, and Muncar. In the first quarter in 1949, Muncar